2015
DOI: 10.1007/s11010-015-2391-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of estrogen receptor β and estrogen-related receptor α gene polymorphisms with bone mineral density in postmenopausal women

Abstract: The aim of the study was to investigate the possible association of AluI and RsaI polymorphisms of estrogen receptor β (ER-β) gene and 23-bp nucleotide repeat polymorphism of estrogen-related receptor α (ERRα) gene with bone mineral density (BMD) in postmenopausal Egyptian women. Two-hundred postmenopausal osteoporotic women as cases and 180 healthy age-matched postmenopausal women as controls were genotyped by PCR fragment length polymorphism for AluI, allele-specific PCR for RsaI, and by sizing of PCR produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…ERβ Rsa I is another important polymorphism of ERβ. Our subgroup analysis revealed a significant association between ERβ Rsa I and PMOP risk in overall populations, which is consistent with the studies of Shoukry et al [ 30 ], and Huang et al [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…ERβ Rsa I is another important polymorphism of ERβ. Our subgroup analysis revealed a significant association between ERβ Rsa I and PMOP risk in overall populations, which is consistent with the studies of Shoukry et al [ 30 ], and Huang et al [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…1 . Fourteen studies [ 11 – 24 ] reported the association between ERα Xba I and PMOP risk, and the number of the included studies that reported the alleles and genotypes of ERα Pvu II, ERα G2014A, ERβ Alu I and ERβ Rsa I was 16 [ 11 – 25 , 32 ], 4 [ 26 – 29 ], 4 [ 17 , 30 32 ] and 2 [ 30 , 31 ], respectively. Ivanova et al [ 20 ], Albagha et al [ 33 ], Aerssens et al [ 24 ], Kurt et al [ 34 ], Ge et al [ 36 ] and Pérez et al [ 19 ] reported both the lumbar spine and femoral neck BMD (g/cm 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many genes with innumerous gene polymorphisms have been identified to be covert risk alleles for osteoporosis vulnerability. Up to now, a series of candidate genes like vitamin D receptor [ 7 , 8 ], estrogen receptors [ 9 , 10 ], osteoprotegerin [ 11 , 12 ], have been widely reported to be associated with osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to identify the genes involved in the pathogenesis of OP, a number of candidate genes, such as the vitamin D receptor (VDR) [7], estrogen receptor (ER) [8,9], and collagen type Ia1 (COLIA1) [10,11] genes, have been examined in association and/or linkage studies; however, they were found to be variably associated with BMD and the risk of OP. Together, these genetic variants only account for a small part of the total genetic variance in osteoporosis; other candidate genes require examination of their contribution to explain the genetic basis of OP.…”
Section: Introductionmentioning
confidence: 99%